Knowledge, Attitudes And Practice Of Hand Hygiene Among Parents Of Nursery Children In Ampang, Selangor: A Pilot Study - Nurul Azmawati Mohamed; Shalinawati Ramli; Nur Natasha Zulkefli Amin; Nooriah Mohamed Salleh; Tengku Zetty Maztura Tengku Jamaludin; Che IIina Che Isahak; Wan Shahida Wan Sulaiman (Sage Publication, 2024)
Introduction: Infections spread easily among children in nurseries due to overcrowding and their natural intimacy. Contact transmission is preventable through proper hand hygiene and good sanitation. This is a pilot study that evaluated knowledge, attitudes and practice (KAP) of hand hygiene among parents. Further study will focus on KAP among parents and caregivers in nurseries and its association with Staphylococcus aureus nasal carriage. Methods :This cross-sectional study involved 30 university support staff who sent their children to nurseries. Participants were given questionnaires consisting statements related to personal hand hygiene, hand hygiene practices during the care of children and infection related to poor hand hygiene. Results :The mean score for knowledge of hand hygiene was 2.71 ±0.257 out of 3. Meanwhile, the mean score for attitude and practice of hand hygiene were 4.59 ±0.395 out of 5 and 4.54 ±0.362 out of 5 respectively. Discussions: Overall results showed that the majority of parents had a good understanding of hand hygiene. However more effort is needed to ensure good hand hygiene technique is taught as early as in nurseries and practiced in the community. This is very important for prevention of communicable diseases in the community